Responsible management in theory and practice in Muslim societies - Sidani, Yusuf M. (Emerald points., 2022)
Responsible Management in Theory and Practice in Muslim Societies delineates principles of responsible management from an Islamic perspective, exploring the concept of responsibility in Islamic religious texts, and how the understanding of responsibility evolved in Islamic jurisprudence. He explains aspects of individual and group responsibility in Islam and the dissonance between theoretical discourse and practical application. Yusuf M. Sidani focuses on the factors that have both facilitated and hampered the application of responsible management principles in practice in this unique context. Themes explored across the book include Islamic texts and responsible leadership, responsibility in Islamic jurisprudence, individual and group responsibilities, and bridging the gap divide between theory and practice in Muslim societies. Sidani also poses proactive questions, including 'Who is a responsible manager?' and 'what does it take to reaffirm both individual and collective responsibilities', and 'whether things can be put back on track again in Muslim societies, and how?'